THE IMAGE OF CHILDREN IN CHARLES DICKENS’ LITERARY WORKS - Safarova Zilola Tolibovna, Maftuna Narzulloyeva Nusratillo qizi (EPRA International Journal of Multidisciplinary Research (IJMR), 2024)
Charles Dickens is a great representative of English Victorian literature who depicted the lives of orphan children. An in-depth analysis of the author’s novels, including, “Great Expectations”, “Oliver Twist”, “Dombey and Son”, “David Copperfield” show the writers mastery in creating images of oppressed children and the childhood experiences of the heroes.